Wear of Hard Dental Tissues and Methods of its Evaluation - P. Holík; Y. Morozova (Czech Dental Chamber, 2018)
Background: In addition to tooth decay, that is the most common disease of hard dental tissues, the dentist often encounters with so-called noncarious lesions. The etiopathogenetic factors of these defects, if not removed, are a frequent cause of conservative therapy failure and should be taken into account during treatment. In the long run, it is not enough just to repair the defect by filling. In case of persistent causes, there is a high risk of re-failure of the reconstruction therapy and recurrence of the problem. The paper summarizes the current knowledge of the clinical manifestations of individual types of noncarious defects, their etiopathogenetic factors, possibilities of diagnostics as well as mechanism by which they can damage hard dental tissues and possibilities of their elimination.